A Review on HT Attacks in PLD and ASIC Designs with Potential Defence Solutions. Issue 1 (2nd January 2018) - Sumathi, G.; Srivani, L.; Thirugnana Murthy, D.; Madhusoodanan, K.; Satya Murty, S.A.V.
ABSTRACT: The tremendous advancement in very large scale integration technology encourages chip designers to rely on commercial electronic design automation tools, offshore fabrication services, and outsourced intellectual property cores. As third-party involvement are more in chip design cycle, integrated circuits (IC) such as programmable logic devices (PLD) and application specific ICs (ASIC) are highly vulnerable to hardware Trojan (HT) attacks. HTs are malicious additions or modifications to existing circuit elements, which can be inserted at any stages of IC life cycle to modify/destroy the functionality, reduce reliability, leak sensitive information, etc. Besides, HT can be designed either as always on or triggered only under certain operating conditions. For example, HT attacks in safety critical applications such as nuclear power plant, space and defence will jeopardise the safety and security of the unit and cause serious consequences. Hence, it is most important to ensure that the chip being in use performs only the intended function. In this paper, an in-depth analysis of feasible HT attacks in PLD and ASIC life cycles are presented. Based on the extensive literature survey on HTs and their countermeasure techniques, the state of the art HT prevention, detection, and diagnosis techniques are recommended to the valid stages of PLD and ASIC life cycles. Therefore, incorporating possible HT defence solutions in respective phases of PLD/ASIC-based safety systems thwart them against HT attacks.